2014
DOI: 10.1002/cncy.21443
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with reduced accuracy in Papanicolaou tests for patients with invasive cervical cancer

Abstract: BACKGROUND: Recent proposals to lengthen the interval in cervical cancer screening highlight the importance of the accurate interpretation of screening tests. Tumor debris present in Papanicolaou (Pap) tests from women with invasive cancer is known to hamper interpretation. The current study evaluated limiting factors in Pap tests from women with invasive cervical cancer. METHODS: A total of 3003 women with the spectrum of cervical lesions who had ThinPrep (Hologic Inc, Marlborough, Mass) Pap and human papillo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 34 publications
1
24
1
1
Order By: Relevance
“…Furthermore, cellularity, cell coating and spreading patterns on the slide seem to seriously affect the screening process. Small to large empty spaces between cell aggregates and isolated, scattered cells affect the screener's observation under bright‐field microscopes by decreasing the level of orientation on the entire slide . This leads consequently to an increased level of uncertainty during the slides' scanning affecting drastically the complete detection of cytomorphologically abnormal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cellularity, cell coating and spreading patterns on the slide seem to seriously affect the screening process. Small to large empty spaces between cell aggregates and isolated, scattered cells affect the screener's observation under bright‐field microscopes by decreasing the level of orientation on the entire slide . This leads consequently to an increased level of uncertainty during the slides' scanning affecting drastically the complete detection of cytomorphologically abnormal cells.…”
Section: Discussionmentioning
confidence: 99%
“…The 45 adenocarcinoma cases described here were extracted from our previous descriptions of this population . The de‐identified ThinPrep slides were retrospectively reviewed for key cytologic elements (see below) without knowledge of the original cytologic interpretation.…”
Section: Methodsmentioning
confidence: 99%
“…For the reviewers who participated in the consensus meetings, an adequate sample had to contain 8,000-12,000 squamous epithelial cells, to be preserved and displayed, and to exclude endocervical cells and metaplastic squamous cells, which were considered in this assessment. Other factors, such as obscuring thick areas, purulence, cytolysis, desiccation, and staining, were also deliberated in the analysis of up to 75% of the smears [23] . In agreement with our findings, in 2014 Zhao et al [23] evaluated 3,003 Pap smears to assess the limitations of cytological examination and found that scant cellularity and the presence of obscuring blood were the most frequent factors in the evaluated smears.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors, such as obscuring thick areas, purulence, cytolysis, desiccation, and staining, were also deliberated in the analysis of up to 75% of the smears [23] . In agreement with our findings, in 2014 Zhao et al [23] evaluated 3,003 Pap smears to assess the limitations of cytological examination and found that scant cellularity and the presence of obscuring blood were the most frequent factors in the evaluated smears.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation